Modified Kraske Procedure with Mid-Sacrectomy and Coccygectomy for En Bloc Excision of Sacral Giant Cell Tumors - Vítor M. Gonçalves; Álvaro Lima; João Gíria; Nuno Carvalho; José Parreira; Manuel Cunha e Sá (Case Reports in Surgery)
Sacral giant cell tumors are rare neoplasms, histologically benign but potentially very aggressive due to the difficulty in achieving a complete resection, their high recurrence rate, and metastization capability. Although many treatment options have been proposed, en bloc excision with tumor-free margins seems to be the most effective, being associated with long term tumor control, improved outcome, and potential cure. An exemplifying case of a 29-year-old female with progressive complaints of pain and paresthesias in the sacral and perianal regions, constipation, and weight loss for 6 months is presented. The surgical technique for en bloc excision of a large sacral giant cell tumor through a modified Kraske procedure with mid-sacrectomy and coccygectomy is described. Complete resection with wide tumor-free margins was achieved. At 5 years of follow-up the patient is neurologically intact, without evidence of local recurrence on imaging studies. A multidisciplinary surgical procedure is mandatory to completely remove sacral tumors. In the particular case of giant cell tumors, it allows minimizing local recurrence preserving neurovascular function, through a single dorsal and definitive approach.